THE CONCEPT OF AN IDEAL PERSON IN WORKS OF ARISTOTLE - Makarevičs, Valērijs; Iliško, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The issue of a human person, and his/her development, and particularly in connection with a social sphere is extremely relevant for our times. In psychology, this issue has been developed through developmental periods, theories of personality identity and conditions that contribute to a self-actualization of an individual. In this regard, interest is how these ideas evolved in the process of cultural and historical development of humankind, how they were understood by previous generations of scientists and philosophers, how theoretical views of past generations are interpreted by the researchers of our time. This determined the objectives of this research. The authors applied the method of content analysis of the text with the aim to discover the concept of an ideal, or perfect person in works of Aristotle, to compare this concept with the corresponding views of Plato, to determine the influence of Aristotle's concept of an ideal person on modern theories of personality. The research method is a content analysis of works of Aristotle and research done by the authors that reflect a philosophical heritage of the Greek thinker. As for both, Plato and Aristotle, the soul is the basis of life and the source of human activity. For Plato the soul appears to be an indivisible and immortal entity, then for Aristotle it has its own structure. Human soul is capable of development and improvement. The main condition for improvement, according to Plato, are correct actions of a person from the point of view of law and public opinion. Aristotle believes that in this process, education and upbringing plays major attention. Aristotle's ideas today are being developed in a deep and humanistic psychology and developmental psychology.